2010
DOI: 10.1177/1528083709357975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Knit Structure and Finishing Treatments on Functional and Comfort Properties of Cotton Knitted Fabrics

Abstract: This study demonstrated that the changes in functional and comfort properties of knitted cotton fabrics were determined by the knitted structure as well as type and concentration of finishing agent. To improve the comfort properties, one should ensure the smoothness of fabric surface, air permeability, heat transmittance as well as hydrophilicity of the knitted fabrics, by selecting the proper knit structure and/or by applying the proper finish such as bio-finish. Soft-finished fabric samples had lower tendenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 11 publications
0
20
0
4
Order By: Relevance
“…Textile substrates, particularly of natural source, are adequate source for the suitable growth of bacteria as they deliver the circumstances like moisture, temperature, oxygen, and nutrients that are vital for their growth [28]. Cellulosic fabrics, especially cotton is extensively employed in the field of clothing due to their renewability, ecofriendly, hydrophilic properties, air permeability and comfort ability [29]. However, cellulose-based textiles are carriers of micro-organisms and more liable to bacterial attack than synthetic textiles; due to their properties of porosity, hydrophilic nature along with the ability to maintain water, oxygen, and nutrients, they promote bacterial growth, body odor, and also loss performance properties [30].…”
Section: Antibacterial Activitiesmentioning
confidence: 99%
“…Textile substrates, particularly of natural source, are adequate source for the suitable growth of bacteria as they deliver the circumstances like moisture, temperature, oxygen, and nutrients that are vital for their growth [28]. Cellulosic fabrics, especially cotton is extensively employed in the field of clothing due to their renewability, ecofriendly, hydrophilic properties, air permeability and comfort ability [29]. However, cellulose-based textiles are carriers of micro-organisms and more liable to bacterial attack than synthetic textiles; due to their properties of porosity, hydrophilic nature along with the ability to maintain water, oxygen, and nutrients, they promote bacterial growth, body odor, and also loss performance properties [30].…”
Section: Antibacterial Activitiesmentioning
confidence: 99%
“…However, the authors did not study the interlock structure and the effect of knitting machine gauge. Ibrahim et al [13] studied the effect of knitting structure and finishing treatments on the comfort properties of textiles. They concluded that single jersey fabric takes longer to absorb water droplet as compared with single pique fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Постановка завдання. Відома робота [9], в якій досліджено вплив заключної обробки бавовняного трикотажного полотна (пом'якшення, біо-, антибактеріальна та водовідштовхуюча обробки) та виду його переплетення на функціональні та гігієнічні властивості текстильного матеріалу.…”
Section: матеріалознавство індустрії моди технологій виробництва текunclassified
“…Трикотаж стає все більш популярним матеріалом для виготовлення одягу. Так за результатами, що представляє Українська асоціація підприємств легкої промисловості [1], у 2017 р. виробництво, а отже і споживання, одягу з трикотажу більше, ніж з тканин у 1,3 рази.…”
unclassified